Mesenchymal stem cells to augment therapeutic angiogenesis in hind-limb ischemia models: how important is their source? - Duffy, Garry P (BioMed Central, 2013)
Murine models of hind-limb ischemia are frequently used to assess interventions aimed at improving therapeutic angiogenesis in critical limb ischemia. Much of the current focus of angiogenesis lies with mesenchymal stem cells (MSCs). Important considerations when using these models include the strain of mouse, because some strains recover from ischemia more rapidly than others, and the MSC source. MSCs derived from certain strains generate increased levels of growth factors such as vascular endothelial growth factor. This may significantly affect the limb?s ability to generate collateral vessels.